Motivations of paying zakat on income: evidence from Malaysia - Abu Bakar, Nur Barizah; Ab. Rashid, Hafiz-Majdi (Canadian Center of Science and Education, 2010)
Zakat on income is one of the emerging issues among Syariah scholars where they might have varying opinions regarding it. The aim of this paper is to identify factors that may influence the Muslims behaviour towards zakat on income. Academicians from three faculties in the International Islamic University Malaysia (IIUM) were used as sample in this study. They were sent self-developed questionnaires requiring them to indicate their level of agreement on certain factors which might influence them in paying zakat on income. Based on the mean ranking of those who pay zakat, the findings suggest that social, religious and economic factors prevail over the other relatively ‘self-centered’ factors. This study concludes by suggesting that there is a need for proper education on zakat which may eventually help the Ummah to benefit from the noble system of zakat.